PERLINDUNGAN HUKUM TERHADAP ANAK YATIM PIATU DI PANTI ASUHAN TUNAS HARAPAN SAMARINDA DI SAMARINDA - Awang Ramdani Wahyudin (Universitas 17 Agustus 1945 Samarinda, 2013)
Abstract In the protection of children parents are obliged and responsible for , among others , caring and nurturing and educating children , in case parents do not execute this obligation especially in parenting , this task can be performed by an authorized agency for the orphanage which , like is governed by Article 27 of Law No. 23 of 2003 ,